Vertical well pressure and pressure derivative analysis for bingham fluids in homogeneous reservoirs (2011)
This paper presents a technique for interpreting the behavior of pressure and pressure derivative for a Bingham-type fluid in a homogeneous reservoir drained by a vertical well using the TDS technique, by observing the influence of the minimum pressure gradient which characterizes this behavior, and characteristic points which are used for estimating formation permeability, drainage area, and skin factor. The pressure derivative for Bingham Non-Newtonian fluids is presented in the literature for the first time. The higher the minimum pressure gradient, the more asymmetrically concave the pressure derivative becomes. Also, it was observed in closed systems that the late unit-slope pressure derivative coincides with the same one for Newtonian fluids.